Target for generating neutrons and method for manufacturing the same

JP2025027536AActive Publication Date: 2025-02-28NGK CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023132339
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-28
Estimated Expiration
2043-08-15

Smart Images

  • Figure 2025027536000001_ABST
    Figure 2025027536000001_ABST
Patent Text Reader

Abstract

To provide a target for generating neutrons which can suppress generation of blistering.SOLUTION: The target for generating neutrons include a beryllium layer formed of a plurality of beryllium crystal grains with a columnar structure which has grown in the thickness direction, and the beryllium layer has gaps among the beryllium crystal grains.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a neutron generating target and a method for manufacturing the same. [Background technology]

[0002] Neutrons are used in applications such as boron neutron capture therapy (BNCT), which is one type of cancer treatment, neutron diffraction, which is used to analyze and identify the structure of materials, and neutron imaging, a type of non-destructive testing. In addition to the traditional nuclear reactors that have been used as sources of neutrons, accelerators are known that generate neutrons by irradiating accelerated protons onto a metal target. Although there are large accelerators that are several kilometers in size and are used at facilities such as J-PARC and SPring-8, from the perspective of ease of installation, small accelerators (for example, accelerators with an installation area of ​​50 m for the main unit of the device) are preferred. 2 Less than 100 mm is advantageous.

[0003] In small accelerators, the acceleration energy of protons is smaller than in large accelerators, so a target that generates neutrons even with a small energy is required. In this regard, beryllium is known as a material for neutron generation targets used in small accelerators. Here, with beryllium targets, there is a problem that bubbles (bulges) called blistering occur during use, and as these bubbles grow larger, they eventually burst. In other words, the diffusion rate of hydrogen in beryllium is extremely slow, so accelerated irradiated protons remain in the beryllium and turn into hydrogen gas, and the hydrogen gas thus generated appears as blistering.

[0004] Several techniques have been proposed to suppress the occurrence of blistering. For example, Non-Patent Document 1 (T. Rinckel et al., "Target Performance at the Low Energy Neutron Source" Physics Procedia 26, pp.168-177(2012)) proposes increasing the acceleration energy of protons and thinning the thickness of the target to allow protons to pass through the target without being retained therein, and to stop the protons in the cooling water on the back side of the target. In addition, Patent Document 1 (Japanese Patent No. 6713653) discloses that, regarding a neutron generating target having a neutron generating target material containing beryllium and a blistering-resistant intermediate material made of a metal capable of storing hydrogen, the thickness of the neutron generating material is equal to or less than the range of the incident protons. With such a neutron generating target, it is said that irradiated protons stop at the blistering-resistant intermediate material, thereby suppressing the hydrogenation of protons inside the neutron generating target material, and thus suppressing the occurrence of blistering. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6713653 [Non-patent literature]

[0006] [Non-Patent Document 1] T. Rinckel et al., "Target Performance at the Low Energy Neutron Source", Physics Procedia 26, pp.168-177(2012) Summary of the Invention

[0007] However, when the acceleration energy of protons is increased, there is a problem that the accelerator, radiation shield, etc. must be increased in size. Furthermore, when the target is made thin, the amount of neutrons generated may decrease, and the mechanical strength of the structure may decrease. Therefore, a neutron generating target that can suppress the occurrence of blistering regardless of the acceleration energy of protons, the thickness of the target, etc. is desired.

[0008] The present inventors have now discovered that it is possible to provide a neutron generation target that is capable of suppressing the occurrence of blistering by providing gaps between the beryllium crystal grains in a beryllium layer composed of a plurality of beryllium crystal grains.

[0009] Therefore, an object of the present invention is to provide a neutron generating target capable of suppressing the occurrence of blistering.

[0010] According to the present invention, the following aspects are provided. [Aspect 1] A neutron generating target comprising a beryllium layer composed of a plurality of beryllium crystal grains having a columnar structure grown in a thickness direction, the beryllium layer having gaps between the plurality of beryllium crystal grains. [Aspect 2] 2. The neutron generation target according to claim 1, wherein the plurality of beryllium crystal grains form a frost columnar structure as a whole. [Aspect 3] 3. The neutron generation target according to aspect 1 or 2, wherein the center-to-center distance between adjacent beryllium crystal grains is 2 to 50 μm. [Aspect 4] 4. The neutron generation target according to any one of aspects 1 to 3, wherein the beryllium crystal grains have an aspect ratio of 1 to 3,000. [Aspect 5] 5. The neutron generation target according to any one of aspects 1 to 4, wherein the beryllium layer is permeable to helium gas. [Aspect 6] 6. The neutron generation target according to any one of aspects 1 to 5, wherein the beryllium layer is a physical vapor deposition film. [Aspect 7] 7. The neutron generation target according to any one of aspects 1 to 6, wherein the beryllium layer has a thickness of 0.02 to 6 mm. [Aspect 8] A neutron generation target according to any one of aspects 1 to 7, further comprising a substrate on one surface of the beryllium layer. [Aspect 9] 9. The neutron generating target of claim 8, wherein the substrate is made of copper. [Aspect 10] A method for manufacturing a neutron generating target, comprising growing a plurality of beryllium crystal grains on one surface of a substrate in a thickness direction of the substrate by physical vapor deposition, thereby obtaining a beryllium layer having gaps between the plurality of beryllium crystal grains. [Aspect 11] A method for producing a neutron generation target according to aspect 10, wherein the physical vapor deposition method is at least one selected from the group consisting of a resistance heating vapor deposition method, an electron beam vapor deposition method, and a sputtering method. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a neutron generation target of the present invention. [Diagram 2] 1 is a graph plotting leak rate versus elapsed time in a helium leak test using the beryllium target of Example 1. [Diagram 3] 1 is a graph plotting leak rate against elapsed time in a helium leak test using the beryllium target of Example 2. [Figure 4] 1 is an SEM image (magnification 1000x) of the beryllium target of Example 1 observed from directly above. [Diagram 5] 1 is an SEM image (magnification 3000x) of the beryllium target of Example 1 observed from directly above. [Figure 6] 1 is an SEM image (magnification: 500x) of a polished cross section of the beryllium target of Example 1. [Figure 7]1 is an SEM image (magnification: 2000 times) of a polished cross section of the beryllium target of Example 1. [Figure 8] 1 is an optical microscope image (magnification: 200 times) of a cross section of the beryllium target of Example 2 after etching. [Figure 9] 1 is an optical microscope image (magnification: 500x) of a cross section of the beryllium target of Example 2 after etching. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Neutron generation target As conceptually shown in FIG. 1, a neutron generation target 10 of the present invention includes a beryllium layer 12. If desired, the neutron generation target 10 may further include a substrate 14 on one surface of the beryllium layer 12. The beryllium layer 12 is composed of a plurality of beryllium crystal grains 12a. Each of the beryllium crystal grains 12a has a columnar structure grown in the thickness direction of the beryllium layer 12. The beryllium layer 12 has gaps between the plurality of beryllium crystal grains 12a. In this way, by providing gaps between the beryllium crystal grains 12a in the beryllium layer 12 composed of a plurality of beryllium crystal grains 12a, a neutron generation target 10 capable of suppressing the occurrence of blistering can be provided.

[0013] Conventional beryllium targets are generally made of a beryllium block material (sintered body), and therefore no gaps exist between the beryllium crystal grains. For this reason, as described above, it is believed that accelerated irradiated protons remain in the beryllium layer and turn into hydrogen gas, causing blistering. In contrast, in the neutron generation target 10 of the present invention, even if accelerated irradiated protons turn into hydrogen gas in the beryllium layer 12, this hydrogen gas is released to the outside through the gaps between the beryllium crystal grains 12a. Therefore, it is possible to suppress the occurrence of blistering regardless of the acceleration energy of the protons, the thickness of the beryllium layer 12, etc.

[0014] Each of the multiple beryllium crystal grains 12a constituting the beryllium layer 12 is preferably composed of simple beryllium metal. However, as long as the desired amount of neutrons can be generated, the beryllium layer 12 may contain beryllium compounds, beryllium alloys, etc., in addition to simple beryllium metal. The beryllium layer 12 may also contain unavoidable impurities resulting from the raw material components, the film formation process, etc.

[0015] As shown in FIG. 1, each of the beryllium crystal grains 12a has a columnar structure that grows in the thickness direction of the beryllium layer 12. According to a preferred embodiment of the present invention, the plurality of beryllium crystal grains 12a form a frost columnar structure as a whole. With such a structure, the beryllium layer 12 has three-dimensional gaps between the crystal grains, and the release of hydrogen gas generated inside the beryllium layer 12 is more efficiently performed, resulting in more effective suppression of the occurrence of blistering. In the schematic diagram shown in FIG. 1, each of the beryllium crystal grains 12a is depicted as extending uniformly from the lower surface to the upper surface of the beryllium layer 12, but the beryllium crystal grains 12a are not limited to this structure, and may have grain boundaries between the upper and lower surfaces of the beryllium layer 12.

[0016] The center-to-center distance between adjacent beryllium crystal grains 12a is preferably 2 to 50 μm, and more preferably 2 to 25 μm. Within this range, hydrogen gas is released more efficiently, and as a result, the occurrence of blistering is more effectively suppressed. The center-to-center distance of the crystal grains can be measured by observing the cross section of the beryllium layer 12 with a scanning electron microscope.

[0017] The beryllium crystal grains 12a preferably have an aspect ratio of 1 or more, more preferably 2 or more, and even more preferably 5 or more. Within such a range, hydrogen gas generated within the beryllium layer 12 is more likely to move in the thickness direction of the beryllium layer 12, and as a result, the occurrence of blistering is more effectively suppressed. The upper limit of the aspect ratio of the beryllium crystal grains 12a is not particularly limited, but is typically 200 or less. In the present invention, the aspect ratio of the beryllium crystal grains 12a refers to the maximum length L of the beryllium crystal grains 12a in the width direction of the beryllium layer 12. w The maximum length L of the beryllium crystal grains 12a in the thickness direction of the beryllium layer 12 T The ratio (=L T / L w The maximum length L of the beryllium crystal grains 12a in the width direction of the beryllium layer 12 is w is not particularly limited, but is typically 2 to 50 μm. T Although not particularly limited, the maximum length L is typically 2 μm or more. W , maximum length L T The aspect ratio can be measured by observing the cross section of the beryllium layer 12 with a scanning electron microscope.

[0018] The beryllium layer 12 is preferably permeable to helium gas. Here, the kinetic molecular diameter of helium is 0.26 nm, which is slightly smaller than the hydrogen molecular diameter of 0.289 nm. Therefore, when the beryllium layer 12 is permeable to helium gas, it can be said that hydrogen gas is also more easily discharged from the beryllium layer 12. In the present invention, "having helium gas permeability" means that a helium gas leak is detected when a helium leak test is performed in accordance with the vacuum spray method (spray method) specified in Annex 1 of JIS Z2331:2006. For example, in a helium leak test, the leak rate (Pa·m) detected by a leak detector after spraying helium gas is 3It is preferable that the maximum value of the leak rate ( / s) is 10 times or more (preferably 100 times or more) larger than the leak rate detected by the leak detector before the helium gas is sprayed.

[0019] The beryllium layer 12 preferably has a thickness of 0.02 to 6 mm. Within this range, it becomes easier to generate a desired amount of neutrons and sufficient strength as a target can be ensured. The surface area of ​​the beryllium layer 12 in plan view (i.e., the surface area of ​​the surface irradiated with protons) can be appropriately determined according to the specifications of the neutron generator (e.g., a small accelerator) used, and is not particularly limited, but is typically 30 to 400 cm. 2 It is.

[0020] The beryllium layer 12 may be formed by any method, but is preferably a physical vapor deposition film. A preferred method for fabricating the neutron generating target 10 including the beryllium layer 12 is described below.

[0021] 1, the neutron generation target 10 may further include a substrate 14 on one side of the beryllium layer 12. The substrate 14 can function as a member for cooling the beryllium layer 12 irradiated with accelerated protons.

[0022] The substrate 14 is preferably made of copper, which allows for more efficient cooling of the beryllium layer 12. The thickness of the substrate 14 is not particularly limited, but is typically 0.1 mm or greater.

[0023] Method for manufacturing neutron generating targets According to a preferred embodiment of the present invention, there is provided a method for manufacturing a neutron generation target 10. This method includes growing a plurality of beryllium crystal grains 12a on one surface of a substrate 14 in the thickness direction of the substrate 14 by physical vapor deposition. In this manner, a beryllium layer 12 having gaps between the plurality of beryllium crystal grains 12a can be obtained.

[0024] Preferred examples of the physical vapor deposition method include resistance heating vapor deposition, electron beam vapor deposition, and sputtering, and more preferred are resistance heating vapor deposition and electron beam vapor deposition, which are economical. -2 It is preferable to perform deposition until the beryllium layer reaches a desired thickness by heating the raw material beryllium to 1287°C (melting point of beryllium) or higher under conditions of 100 Pa or less and a substrate temperature of 350 to 550°C. Film formation by electron beam deposition may be performed under the same conditions as the resistance heating deposition method described above, except that the voltage and current are controlled so that the beryllium melts. Film formation by sputtering may be performed by creating a high vacuum in the chamber, filling it with Ar gas to about 1 Pa, and applying a voltage between the substrate and the beryllium until the beryllium layer reaches a desired thickness.

[0025] Beryllium as a raw material for the physical vapor deposition method is preferably obtained by processing a beryllium ingot produced by vacuum casting into small pieces. The purity of the beryllium ingot is preferably 98% by weight or more, more preferably 99% by weight or more. EXAMPLES

[0026] The present invention will now be further illustrated by the following examples.

[0027] Example 1 As a neutron generating target according to the present invention, a beryllium target was prepared by the following procedure.

[0028] (1) Preparation of beryllium ingot A beryllium ingot (purity 99% by weight) obtained by vacuum casting was prepared. This beryllium ingot was manufactured as follows. First, granular metallic beryllium was placed in a magnesium oxide crucible in a vacuum melting furnace, and the furnace was kept at about 1300°C until the beryllium was melted. After the beryllium was completely melted, the temperature and degree of vacuum of the furnace were increased to remove impurities. After refining in the vacuum melting furnace was thus completed, the melt was poured into a graphite crucible in a vacuum and solidified to produce a beryllium ingot.

[0029] (2) Preparation of targets by physical vapor deposition The prepared beryllium ingot was cut into small pieces, which were then placed in a crucible in a vacuum chamber. A 0.12 mm thick beryllium layer was formed on one surface of a commercially available pure copper plate (thickness: 0.15 mm) prepared as a deposition substrate by resistance heating deposition using the following equipment and conditions. - Equipment: Resistance heating deposition equipment (manufactured by Sanyu Electronics Co., Ltd., product number: SVC-700TMSG / 7PS80) - Beryllium heating temperature: 1300℃ - Deposition time: 60 minutes - Vacuum degree: 2×10 -2 Pa or less - Substrate temperature: 450℃

[0030] For various evaluations described later, the pure copper plate after the beryllium layer was formed was etched away with nitric acid to obtain a beryllium target having a diameter of 50 mm and a thickness of 0.12 mm.

[0031] Example 2 (comparison) Beryllium targets were fabricated by the conventional powder sintering method. The specific procedure is as follows.

[0032] (1) Preparation of beryllium ingot A beryllium ingot similar to that in Example 1 was prepared.

[0033] (2) Preparation of targets by powder sintering The prepared beryllium ingot was mechanically crushed and then sieved to obtain beryllium powder with a grain size of 300 mesh. This beryllium powder was sintered by a vacuum hot press method to obtain a molded body. Specifically, the beryllium powder was filled into a mold in a vacuum furnace, and a pressure of 8 MPa was applied in the vertical direction while vacuum heating in a temperature range of 1025 to 1125 ° C. to obtain a molded body. This molded body was cut to a thickness of 10 mm, and hot rolling and softening annealing were repeated. At this time, the hot rolling and softening annealing were both performed in a temperature range of 750 to 950 ° C. In this way, a beryllium target with a diameter of 50 mm and a thickness of 0.025 mm was obtained.

[0034] Various evaluations The beryllium targets obtained in Examples 1 and 2 were subjected to the following various evaluations.

[0035] <Helium leak test> A helium leak test was conducted on the beryllium target in accordance with the vacuum spray method (spray method) of JIS Z2331:2006. Specifically, the beryllium target was fixed to a sample holder inside the test piece (workpiece) connected to a leak detector (ULVAC, Inc., HELIOT901W1). After evacuating the inside of the test piece, helium gas was sprayed from the outside of the test piece using a spray probe, and the helium gas that leaked into the test piece was detected by the leak detector. Helium gas was sprayed twice for each example.

[0036] As a result of the helium leak test, the beryllium target in Example 1 leaked gas with each helium gas blow (maximum leak rate: about 5×10 -5 Pa·m 3 / s) was detected. The leak rate before the helium gas was sprayed was approximately 2×10 -7 Pa·m 3 / s. Therefore, it was confirmed that the beryllium target of Example 1 had gaps large enough to be permeable to helium. Here, the dynamic molecular diameter of helium is 0.26 nm, which is slightly smaller than the hydrogen molecular diameter of 0.289 nm. Therefore, when the accelerated irradiated protons become hydrogen gas in the beryllium target of Example 1, the hydrogen gas is released to the outside of the beryllium target in the same way as helium gas, and as a result, it is considered that the occurrence of blistering is suppressed. For reference, a graph plotting the leak rate against the elapsed time in the helium leak test using the beryllium target of Example 1 is shown in FIG. 2.

[0037] On the other hand, in the case of the beryllium target in Example 2, the leak rate was below the detection limit (1.0 × 10 -14 Pa·m 3 / s), and it was confirmed that the target had no helium permeability. Therefore, when accelerated irradiated protons become hydrogen gas inside the beryllium target of Example 2, it is believed that this hydrogen gas is difficult to release outside the beryllium target, resulting in the occurrence of blistering. For reference, a graph plotting the leak rate against the elapsed time in the helium leak test using the beryllium target of Example 2 is shown in Figure 3.

[0038] <Observation of Beryllium Structure> The beryllium target of Example 1 was observed from directly above using a scanning electron microscope (SEM, manufactured by JEOL Ltd., product number: JSM-6490LA) under conditions of an acceleration voltage of 15 kV and magnifications of 1000 times and 3000 times. The obtained observation images are shown in FIG. 4 (magnification 1000 times) and FIG. 5 (magnification 3000 times). Next, the beryllium target of Example 1 was filled with resin and the cross section was polished. Then, the polished cross section of the beryllium target was observed using the above SEM under conditions of an acceleration voltage of 15 kV and magnifications of 500 times and 2000 times. The obtained observation images are shown in FIG. 6 (magnification 500 times) and FIG. 7 (magnification 2000 times). As shown in FIG. 4 to FIG. 7, it was confirmed that the beryllium target (beryllium layer 12) of Example 1 is composed of a plurality of beryllium crystal grains 12a having a columnar structure, and that there are gaps between the plurality of beryllium crystal grains 12a.

[0039] On the other hand, in the beryllium target of Example 2, it was difficult to confirm the metal structure by SEM observation similar to that of Example 1, so a cross-sectional observation was performed after etching. Specifically, the beryllium target of Example 2 was embedded in resin and the cross-section was polished. The polished cross-section was brought into contact with an etching solution and subjected to an etching process to reveal the metal structure. Then, the cross-section after the etching process was observed at magnifications of 200 times and 500 times using an optical microscope. The obtained observation images are shown in FIG. 8 (magnification 200 times) and FIG. 9 (magnification 500 times). As shown in FIGS. 8 and 9, it was confirmed that the beryllium target of Example 2 has flat crystal grains densely present and has no gaps. [Explanation of symbols]

[0040] 10 Neutron generation target 12 Beryllium Layer 12a Beryllium Grains 14 Substrate

Claims

1. A neutron generating target comprising a beryllium layer composed of a plurality of beryllium crystal grains having a columnar structure grown in a thickness direction, the beryllium layer having gaps between the plurality of beryllium crystal grains.

2. 2. The neutron generating target according to claim 1, wherein the plurality of beryllium crystal grains as a whole form a frost columnar structure.

3. 3. The neutron generating target according to claim 1, wherein the center-to-center distance between adjacent beryllium crystal grains is 2 to 50 μm.

4. 3. The neutron generating target according to claim 1, wherein the beryllium grains have an aspect ratio of 1 to 3,000.

5. 3. The neutron generating target according to claim 1, wherein the beryllium layer is permeable to helium gas.

6. 3. The neutron generating target according to claim 1, wherein the beryllium layer is a physical vapor deposition film.

7. 3. The neutron generating target according to claim 1, wherein the beryllium layer has a thickness of 0.02 to 6 mm.

8. The neutron generating target according to claim 1 or 2, further comprising a substrate on one surface of the beryllium layer.

9. The neutron generating target of claim 8 , wherein the substrate is comprised of copper.

10. A method for manufacturing a neutron generating target, comprising growing a plurality of beryllium crystal grains on one surface of a substrate in a thickness direction of the substrate by physical vapor deposition, thereby obtaining a beryllium layer having gaps between the plurality of beryllium crystal grains.

11. The method for producing a neutron generation target according to claim 10, wherein the physical vapor deposition method is at least one method selected from the group consisting of a resistance heating vapor deposition method, an electron beam vapor deposition method, and a sputtering method.

Citation Information

Patent Citations

  • Manufacture of diaphragm for acoustic equipment

    JP1992144400A

  • Composite target, neutron generating method using composite target, and neutron generator using composite target

    JP2012119062A

  • Neutron generation target, neutron generation device, neutron generation target manufacturing method, and neutron generation method

    JP2016136499A

  • Target structure and target device

    JP2020020714A

  • Neutron generation lithium target and method for manufacturing the same

    JP2021103104A